Pengembangan Media Tata Surya Berbasis Macromedia Flash Sebagai Inovasi Pembelajaran DARING Untuk Siswa SD - Sahari, Sutrisno; Wahyudi (JURNAL PENDIDIKAN DASAR NUSANTARA, 2020)
Abstract: Based on the existing problems, during the Covid-19 pandemic, students were required to learn from home by learning online (DARING). Thus the researcher aims to develop innovative and valid learning media for students. The method used in this study is to use the R&D method with the ADDIE model (Analysis, Design, Development, Implementation and Evaluation). The results showed that the solar system media was suitable for use by elementary school students as evidenced by the results of the validity of the media expert with a validity value of 90% with the feasible category. The validity of media eligibility is based on the suitability of images, colors, fonts, text layout, images, animation and sound. While the validity of material experts reached 83% based on core competence (KI), indicators, suitability with children's cognitive development. Meanwhile, 87% of linguists were categorized as feasible based on the level of language development of students. Thus the solar system media products are valid and suitable for use in learning in elementary schools.